Pengaruh Experiential Marketing dan Perceived Quality tehadap Loyalitas Pelanggan POPIPOP Mie Kuah Pedas Cabang Yosodipuro Surakarta: Pengaruh Experiential Marketing dan Perceived Quality tehadap Loyalitas Pelanggan POPIPOP Mie Kuah Pedas Cabang Yosodipuro Surakarta - Jihan Nur Hidayah Kussudyarsana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tight competition in the culinary industry makes culinary business actors must carry out strategies to increase customer loyalty. For this reason, this study is to analyze the effect of experiential marketing and perceived quality on customer loyalty of POPIPOP Mie Kuah Pedas, Yosodipuro branch. Data were collected from 150 respondents who were customers of POPIPOP Mie Kuah Pedas, Yosodipuro branch. The study employed a purposive sampling strategy to choose participants, followed by data analysis using the SPSS program through multiple regression analysis. The study results show three conclusions, namely Experiential Marketing is significant to Customer Loyalty, Perceived Quality is significant to Customer Loyalty, and Experiential Marketing and Perceived Quality have a simultaneous or joint effect on Customer Loyalty.